Education on the Benefits of Gymnastics Postpartum to Involution Uteri on Postpartum Mothers in Aek Haruaya Village, Portibi District, North Padang Lawas Regency in 2023 - Wulandari, Ratna (IJCS: International Journal of Community Service, 2024)
The postpartum period (peueperium) is the period after childbirth is complete, up to 6 weeks or 42 days. After the postpartum period, the reproductive organs will slowly experience changes like before pregnancy. Postpartum mothers experience recovery in their physical and psychological condition. What is expected in the 6 week period after giving birth is that all of the mother's body systems will recover from the various effects of pregnancy and return to their pre-pregnancy state, one of which is changes in the uterus which gradually recovers to its pre -pregnancy state. Postpartum mothers will experience changes in uterine involution, namely the process of returning the uterus to the state it was in before pregnancy. The uterus will decrease in size in approximately 6 weeks. However, it can be faster if you balance it by doing postpartum exercises. This study aims to determine the effectiveness of postpartum exercise on uterine involution in postpartum mothers.